CRIMINALISTIC CHARACTERISTICS OF CRIMES RELATED TO ILLEGAL ACCESS TO COMPUTER INFORMATION - KHARISOVA Zarina Irekovna (Правовое государство: теория и практика, 2025)
The article shows the need to consider the directions of improving the effectiveness of investigation of crimes related to illegal access to computer information, which is due to their widespread today. The applied significance of the study lies in the possibility of forming on the basis of the criminalistic characteristic of this type of crime private criminalistic methods of investigation of such crimes, creating criminalistic records of digital evidence and developing specialized software in the form of decision support systems used in putting forward investigative versions. The purpose of the research is to describe the elements of the criminalistic characteristics of crimes related to illegal access to computer information, taking into account the modern development of information technology. Research methods: in the course of the study, a set of general (description, generalization and comparison), general scientific (analysis, synthesis, modeling and classification), specific scientific (statistical, cybernetic) methods of cognition is used. Research results: the article describes the elements of the criminalistic characteristics of crimes related to illegal access to computer information, which can be the basis for the formation of an information model (digital t win) of the crime.